Effects of in vitro digestion on protein degradation, phenolic compound release, and bioactivity of black bean tempeh - Wang, Kun; Gao, Yongjiao; Zhao, Jing; Wu, Yue; Sun, Jingchen; Niu, Guangcai; Zuo, Feng; Zheng, Xiqun (Frontiers in Nutrition, 2022)
The nutritional value and bioactivity of black beans are enhanced when fermented as tempeh, but their bioaccessibility and bioactivity after ingestion remain unclear. In this study, black bean tempeh and unfermented black beans were digested in vitro and changes in protein degradation, phenolic compound release, angiotensin I-converting enzyme (ACE)-inhibitory activity, and antioxidant activity between the two groups were compared. We observed that the soluble protein content of digested black bean tempeh was generally significantly higher than that of digested unfermented black beans at the same digestion stage (P < 0.05). The degree of protein hydrolysis and the content of <10 kDa peptides were also significantly higher in the digested black bean tempeh than in digested unfermented black beans (P < 0.05). SDS-polyacrylamide gel electrophoresis (SDS-PAGE) and reversed-phase high-performance liquid chromatography (RP-HPLC) analysis showed that most macromolecular proteins in tempeh had been degraded during fermentation and more of the small peptides were released from black bean tempeh during digestion, respectively. Compared to that of the unfermented black beans, the level of ACE inhibition of black bean tempeh was lower, but this significantly increased to 82.51% following digestion, closing the gap with unfermented black beans. In addition, the total respective levels of phenolics, flavonoids, and proanthocyanidins released from black bean tempeh were 1.21, 1.40, and 1.55 times those of unfermented black beans following in vitro digestion, respectively. Antioxidant activity was also significantly higher in digested black bean tempeh than in digested unfermented black beans and showed a positive correlation with phenolic compound contents (P < 0.05). The results of this study proved that, compared to unfermented black beans, black bean tempeh retained protein and phenolic compound bioaccessibility and antioxidant activity and showed an improved ACE-inhibitory activity even after consumption.